Expanding the Use of a Fluorogenic Method to Determine Activity and Mode of Action of Bacillus thuringiensis Bacteriocins Against Gram-Positive and Gram-Negative Bacteria. (1st August 2012) - de la Fuente-Salcido, Norma M.; Barboza-Corona, J. Eleazar; Espino Monzón, A. N.; Pacheco Cano, R. D.; Balagurusamy, N.; Bideshi, Dennis K.; Salcedo-Hernández, Rubén
Abstract : Previously we described a rapid fluorogenic method to measure the activity of five bacteriocins produced by Mexican strains of Bacillus thuringiensis against B. cereus 183. Here we standardize this method to efficiently determine the activity of bacteriocins against both Gram-positive and Gram-negative bacteria. It was determined that the crucial parameter required to obtain reproducible results was the number of cells used in the assay, that is, ~ 4 × 10 8  cell/mL and ~ 7 × 10 8  cell/mL, respectively, for target Gram-positive and Gram-negative bacteria. Comparative analyses of the fluorogenic and traditional well-diffusion assays showed correlation coefficients of 0.88 to 0.99 and 0.83 to 0.99, respectively, for Gram-positive and Gram-negative bacteria. The fluorogenic method demonstrated that the five bacteriocins of B. thuringiensis have bacteriolytic and bacteriostatic activities against all microorganisms tested, including clinically significant bacteria such as Listeria monocytogenes, Proteus vulgaris, and Shigella flexneri reported previously to be resistant to the antimicrobials as determined using the well-diffusion protocol. These results demonstrate that the fluorogenic assay is a more sensitive, reliable, and rapid method when compared with the well-diffusion method and can easily be adapted in screening protocols for bacteriocin production by other microorganisms.